2002
DOI: 10.1021/jf010850d
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Metolachlor by Fungal Cultures

Abstract: Metabolism of metolachlor was studied using a mixed fungal culture isolated from a metolachlor-acclimated field soil. The culture rapidly degraded metolachlor with a half-life of 3.5 days in broth. Aspergillus flavus and A. terricola purified from the mixed culture also metabolized metolachlor effectively. Five metabolites obtained were identified by co-chromatography on HPLC by comparing with authentic standards and by GC-MS. Hydrolytic dechlorination, N-dealkylation, and amide bond cleavage appeared to be th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
3
11
0
Order By: Relevance
“…The half-life was calculated to be 1.30 days according to the first-order kinetics equation, which proved that MBC exhibited a higher activity to hexazinone degradability than that of individual strains. The synergistic effect of the two isolates in their mixed culture on degradation was present, and Synal & Kulshrestha (2002) also observed the same phenomenon in the metabolism of metolachlor by fungal cultures.…”
Section: Degradation Of Hexazinone By Mbc In Msm and Bacterial Growthsupporting
confidence: 60%
See 1 more Smart Citation
“…The half-life was calculated to be 1.30 days according to the first-order kinetics equation, which proved that MBC exhibited a higher activity to hexazinone degradability than that of individual strains. The synergistic effect of the two isolates in their mixed culture on degradation was present, and Synal & Kulshrestha (2002) also observed the same phenomenon in the metabolism of metolachlor by fungal cultures.…”
Section: Degradation Of Hexazinone By Mbc In Msm and Bacterial Growthsupporting
confidence: 60%
“…At present biological decontamination of pesticidal wastes or spills has become an increasingly important area of research and it is preferable if a microbial or biological method of degradation is available for the various pesticidal compounds (Synal & Kulshrestha 2002). Hexazinone, whose chemical structure is shown in Figure 1, is a broad-spectrum herbicide used to control a wide variety of broad leaf weeds, grasses and woody plants.…”
Section: Introductionmentioning
confidence: 99%
“…A similar decrease in soil biomass throughout the soil profile was previously reported by Willems et al 36 Konopka and Turco10 observed that microbial biomass declined by several orders of magnitude with soil depth. Biodegradation has been shown to be the primary mechanism of metolachlor dissipation in soil 37, 38. In fact, repeated soil application of metolachlor has been found to result in adapted microbial populations that have an enhanced ability to degrade the compound 39.…”
Section: Resultsmentioning
confidence: 99%
“…Microorganisms such as Rhizopus, Actinomyces and Streptomyces isolated from a soil treated with metolachlor for five years mineralised 18.4% of the initial 14 C metolachlor applied (Liu et al, 1988). In addition, Bacillus circulans, B. megaterium, Fusarium sp., Mucor racemosus, Phanerochaete chrysosporium, Rhizoctonia praticola, Syncephalastrum racemosum and actinomycete have also been found to degrade metolachlor (Saxena et al, 1987;Liu et al, 1991, Liu et al, 1995Libra et al, 1996;Sanyal & Kulshrestha, 2002). A mixed culture of Bacillus luciferensis, Stenotrophomonas acidaminiphila and Pseudomonas sp.…”
Section: Microbial Degradationmentioning
confidence: 99%